Lung function after exposure to barley dust. Issue 2 (February 1985) - McCarthy, P E; Cockcroft, A E; McDermott, M
Abstract : Six men handling barley were followed up over two working days and their flow volume curves were measured every two hours. All experienced falls in ventilatory capacity of up to 800 ml with changes in the shape of the flow volume curve in five men. Five volunteers not previously exposed to barley dust sat in a silo for two hours. Decreases in ventilatory capacity ranging from 200 ml to 800 ml were found, with recovery taking up to 72 hours. All subjects had decreases in flow at 50% vital capacity but little or no change in flow at 75% vital capacity. In three subjects there was a drop in specific conductance that lasted for less than 24 hours. Two subjects were similarly exposed on a second occasion when transfer factor for carbon monoxide was measured in addition to flow volume curves. There was a decrease in transfer factor but no change in transfer factor per unit volume (Kco).